Overcoming Instability of Antibody‐Nanomaterial Conjugates: Next Generation Targeted Nanomedicines Using Bispecific Antibodies. Issue 16 (10th June 2016) - Howard, Christopher B.; Fletcher, Nicholas; Houston, Zachary H.; Fuchs, Adrian V.; Boase, Nathan R. B.; Simpson, Joshua D.; Raftery, Lyndon J.; Ruder, Tim; Jones, Martina L.; de Bakker, Christopher J.; Mahler, Stephen M.; Thurecht, Kristofer J.
Abstract : Targeted nanomaterials promise improved therapeutic efficacy, however their application in nanomedicine is limited due to complexities associated with protein conjugations to synthetic nanocarriers. A facile method to generate actively targeted nanomaterials is developed and exemplified using polyethylene glycol (PEG)‐functional nanostructures coupled to a bispecific antibody (BsAb) with dual specificity for methoxy PEG (mPEG) epitopes and cancer targets such as epidermal growth factor receptor (EGFR). The EGFR‐mPEG BsAb binds with high affinity to recombinant EGFR ( K D : 1 × 10 –9 m ) and hyperbranched polymer (HBP) consisting of mPEG ( K D : 10 × 10 –9 m ) and demonstrates higher avidity for HBP compared to linear mPEG. The binding of BsAb‐HBP bioconjugate to EGFR on MDA‐MB‐468 cancer cells is investigated in vitro using a fluorescently labeled polymer, and in in vivo xenograft models by small animal optical imaging. The antibody‐targeted nanostructures show improved accumulation in tumor cells compared to non‐targeted nanomaterials. This demonstrates a facile approach for tuning targeting ligand density on nanomaterials, by modulating surface functionality. Antibody fragments are tethered to the nanomaterial through simple mixing prior to administration to animals, overcoming the extensive procedures encountered for developing targeted nanomedicines. Abstract : The generation of targeted nanomaterials for cancer theranostics by the simple mixing of hyperbranched polyethylene glycol (PEG) polymers with bispecific antibodies (BsAbs) is reported. The BsAbs are specific for methoxy PEG epitopes and cancer cell markers such as epidermal growth factor receptor. The BsAb effectively tethered to methoxy PEG epitopes on the hyperbranched PEG structure and the resulting bio‐conjugate targeted cancer cell markers.